UPAH MINIMUM DALAM PERATURAN MENTERI TENAGA KERJA DAN TRANSMIGRASI NOMOR 7 TAHUN 2013 DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Ayu Yuningsih (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Today the problems of labor and wages have been unsolved problems. The root of the problems that occur in workers or workers still lies in the issues of relations and agreements between employers and governments that ultimately impact on the workers. The Government has arranged a solution to solve the problem of injustice towards the labor of one of them through the determination of Minimum Wages as regulated in the Regulation of Minister of Manpower and Transmigration No. 7 of 2013, but the determination of Minimum Wage for workers is considered not to provide justice for laborers because the value of wages earned is comparable with the large role of labor services in realizing the business results of the company concerned. This paper aims to find out how the Islamic view of Minimum Wage is applied in Indonesia and find out whether the Minimum Wage determination has fulfilled the principles of Maslahah and Adl which are at the core of Islamic teachings.